Group Behavioral Activation for Patients With Severe Obesity and Binge Eating Disorder: A Randomized Controlled Trial. (March 2015) - Alfonsson, Sven; Parling, Thomas; Ghaderi, Ata
The aim of the present study was to assess whether behavioral activation (BA) is an efficacious treatment for decreasing eating disorder symptoms in patients with obesity and binge eating disorder (BED). Ninety-six patients with severe obesity and BED were randomized to either 10 sessions of group BA or wait-list control. The study was conducted at an obesity clinic in a regular hospital setting. The treatment improved some aspects of disordered eating and had a positive effect on depressive symptoms but there was no significant difference between the groups regarding binge eating and most other symptoms. Improved mood but lack of effect on binge eating suggests that dysfunctional eating (including BED) is maintained by other mechanisms than low activation and negative mood. However, future studies need to investigate whether effects of BA on binge eating might emerge later than at post-assessment, as in interpersonal psychotherapy for bulimia nervosa.